RESPONSIVE EVALUATION OF INCLUSIVE ISLAMIC RELIGIOUS EDUCATION FOR CHILDREN WITH DISABILITIES IN SPECIAL SCHOOLS - Karnadi Karnadi; Dwi Istiyani; Nasikhin Nasikhin; Waliyadin Waliyadin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze how religious education for children with disabilities is implemented in Islamic educational institutions to support students' spiritual development, using Stake's Responsive Evaluation Model. Despite the global expansion of inclusive education, religious learning for students with disabilities remains underdeveloped, particularly in terms of adaptive pedagogy and contextual learning approaches. Existing practices often rely on generic teaching models that do not adequately address diverse learning needs, thus limiting students' engagement and spiritual development. The study employed a qualitative case study approach utilizing in-depth interviews, participant observation, and document analysis. Data were analyzed using an interactive model and interpreted through a Responsive Evaluation framework that focuses on antecedents, transactions, and outcomes. Findings revealed that an integrative model of inclusive religious education emerged through the alignment of accessible learning environments and adaptive pedagogy. Adaptive pedagogical interactions served as a mediating mechanism, enhancing student engagement and understanding through simplified language, repetition, and multisensory strategies. Students' spiritual development was primarily fostered through experiential and contextual learning, which enabled the internalization of meaningful religious values. The research findings advance inclusive Islamic education by proposing a comprehensive framework that integrates environmental, pedagogical, and experiential dimensions